2012
DOI: 10.5483/bmbrep.2012.45.5.287
|View full text |Cite
|
Sign up to set email alerts
|

FGF-2 inhibits TNF-α mediated apoptosis through up-regulation of Bcl2-A1 and Bcl-xL in ATDC5 cells

Abstract: FGF-2 is involved in cell survival

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Bcl2 downregulation has been shown to increase caspase-3 in breast cancer cells (25). Furthermore, Bcl2A mediates anti-apoptotic effects of fibroblast growth factor in chrondogenic progenitor-like cell line (26). Therefore, these pathways may be involved in reducing/counteracting caspase-3 activity in hemSCs but not mature endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl2 downregulation has been shown to increase caspase-3 in breast cancer cells (25). Furthermore, Bcl2A mediates anti-apoptotic effects of fibroblast growth factor in chrondogenic progenitor-like cell line (26). Therefore, these pathways may be involved in reducing/counteracting caspase-3 activity in hemSCs but not mature endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the effect of the antibody on the growth of cells, an MTT assay was performed as described previously [48, 49]. Cells were treated with PBS, normal IgG, or anti-TM4SF5 monoclonal antibody (10 μg/ml) for up to 5 days.…”
Section: Methodsmentioning
confidence: 99%
“…Low doses of endogenous TNF-α produced by normal epithelial cells or epithelial-derived cancer cells can also act as a tumor promoter, in NSCLC cells, the TNF-α expression may affect the normal lung adjacent to the tumor [27], in human breast cancer cell, TNF-α enhanced invasiveness of the malignant cells dependent on matrix metalloprotease [28], in ovarian cancer cells the CXCR4 expression also in a TNF-α–dependent manner [29]. Many studies have demonstrated the role of TNF-α in cell proliferation, and some reports have shown that TNF-α acts as an apoptotic mediator in some cell lines, such as hematopoietic cells [30] and cartilage progenitor cells [31]. This proapoptotic effect can be weakened by other substances in the body, such as miRNAs.…”
Section: Introductionmentioning
confidence: 99%